Building a ‘dream team’: Cross-cultural entrepreneurship at QuikForce - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2016)
It was May 2016, and Desmond Lim, CEO and co-founder of QuikForce, a moving and logistics company based in Boston, U.S., had just concluded a five-hour long meeting with his team. QuikForce had been founded to simplify the stressful moving process for both the customer and movers, by acting as an intermediary that provided a technology platform which would pair potential customers with suitable moving companies based on their moving requirements. Ten months had flown by since the QuikForce website was first launched, and within two months of its launch, QuikForce was profitable. The meeting left two questions on Lim's mind. First, given QuikForce's initial success, should he begin to establish a presence in his home country, Singapore, or at least in Asia? The meeting with his team saw opinions split among three options\342\200\224(a) broadening the service offerings in the company's existing U.S. locations (Boston, New York and Miami), (b) expanding to new cities in the U.S., or (c) pursuing expansion into Asia. Lim knew that a decision was looming. Second, was his present team the 'dream team' that would be able to take this company forward to the next level? This case is designed to help students think critically about the key challenges related to leading a start-up team and trade-offs faced. Through classroom discussion, students should also be encouraged to reflect on their own leadership skills and development trajectory.\302\240